Dow Performance Silicones' new masterbatch extends slip options for form-fill-seal packaging. Issue 12 (December 2018) - Unknown
Abstract : New silicone-based product Dow Corning™ MB25-235 Masterbatch offers stable, efficient slip performance coupled with broad food contact compliance for form-fill-seal (FFS) applications. Developed by Dow Performance Silicones, a global business unit of DowDuPont Specialties Products division, the new masterbatch significantly reduces the coefficient of friction (COF) of low density polyethylene (LDPE) film to optimize flexible packaging production. The product was unveiled at Fakuma 2018 in October.